Chocolate Pathway to the Gods. - Dreiss, Meredith L. (University of Arizona Press, 2008)
"Chocolate: Pathway to the Gods takes readers on a journey through 3,000 years of the history of chocolate. It is a trip filled with surprises. And it is a beautifully illustrated tour, featuring 132 color photographs and a captivating sixty-minute DVD documentary. Along the way, readers learn about the mystical allure of chocolate for the peoples of Mesoamerica, who were the first to make it and who still incorporate it into their lives and ceremonies today." "Although it didn't receive its Western scientific name, Theobroma cacao - "food of the gods" - until the eighteenth century, the cacao tree has been at the center of Mesoamerican mythology for thousands of years. Not only did this "chocolate tree" produce the actual seeds from which chocolate was extracted but it was also symbolically endowed with cosmic powers that enabled a dialogue between humans and their gods. From the pre-Columbian images included in this book, we are able to see for ourselves the importance of chocolate to the Maya, Aztecs, Olmecs, Mixtecs, and Zapotecs who grew, produced, traded, and fought over the prized substance." "Through archaeological and other ethnohistoric research, the authors of this book document the significance of chocolate - to gods, kings, and everyday people - over several millennia. The illustrations allow us to envision the many ancient uses of this magical elixir: in divination ceremonies, in human sacrifices, and even in ball games. And as mythological connections between cacao trees, primordial rainforests, and biodiversity are unveiled, our own quest for ecological balance is reignited. In demonstrating the extraordinary value of chocolate in Mesoamerica, the authors provide new reasons - if any are needed - to celebrate this wondrous concoction."--BOOK JACKET.